2009
DOI: 10.1002/uog.6292
|View full text |Cite
|
Sign up to set email alerts
|

Four‐dimensional ultrasonographic imaging of fetal lower urinary tract obstruction and guidance of percutaneous cystoscopy

Abstract: Fetal cystoscopy may be an option for the treatment of severe lower urinary tract obstruction 1 -7 . In the present case the use of four-dimensional (4D) ultrasonography was helpful in the identification of the urethral obstruction and guidance of percutaneous cystoscopy.A 34-year-old pregnant woman, gravida 2 para 1 (one previous vaginal delivery), was referred at 20 weeks' gestation because her male fetus presented with distended bladder, dilated proximal urethra ('keyhole sign') ( Figure 1a), bilateral hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 9 publications
0
21
0
Order By: Relevance
“…Fetal cystoscopy allows an endoscopic examination of the dilated posterior urethra and identification of PUV, UA, or US. Previous studies have demonstrated that the etiology of LUTO is one of the major factors associated with prognosis …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fetal cystoscopy allows an endoscopic examination of the dilated posterior urethra and identification of PUV, UA, or US. Previous studies have demonstrated that the etiology of LUTO is one of the major factors associated with prognosis …”
Section: Resultsmentioning
confidence: 99%
“…11,[13][14][15] Fetal cystoscopy has been described as an alternative option to VAS by avoiding amnioinfusion, by providing an etiological diagnosis for the obstruction prior to prenatal management, and consequently by directing the specific prenatal treatment for the cause of LUTO. [16][17][18][19][20][21][22][23][24][25] However, there are limited data on outcomes after fetal cystoscopy, especially those outcomes related to long-term follow-up. In addition, significant perinatal complications have been reported related to the surgical techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Because congenital LUTO is associated with increased perinatal and infant mortality and morbidity, a series of antenatal interventions have been proposed in an attempt to prevent postnatal complications4, 13, 15–20, 28–34. The optimal management of fetuses with LUTO continues to be one of the most challenging subjects in the field of fetal intervention and therapy3.…”
Section: Discussionmentioning
confidence: 99%
“…Percutaneous fetal cystoscopy has been reported as an alternative therapeutic option for the in‐utero treatment of LUTO. It has theoretical advantages over VAS, as it allows anatomical diagnosis and ablation of the PUV (if visualized) by direct instrumentation of the proximal urethra4, 15–21, 29, 32. However, if urethral atresia is identified, ablation cannot be performed and prenatal therapy is not possible, unless a VAS is placed in situ .…”
Section: Discussionmentioning
confidence: 99%
“…Fetal cystoscopy appears promising as both a diagnostic and therapeutic intervention. However, it remains technically challenging and requires refinements in current equipment to improve its overall success rate [19][20][21] . In our study, despite a trend towards increased overall success rate with F-VASI, there was no statistically significant difference compared with US-VASI (90 vs. 77%, p = 0.3).…”
Section: Discussionmentioning
confidence: 99%